Comparative evaluation of intraligamentary injection and traditional inferior alveolar nerve block in endodontic management of mandibular molar with symptomatic irreversible pulpitis: A randomized double-blinded clinical trial - Tekam, Deepashri; Chetana S Makade; Pratima R Shenoi; Mohit K Gunwal (Asian Journal of Medical Sciences, 2024)
Background: Intraligamentary anesthesia (ILA) injection using a single-tooth anesthesia (STA) system has been used as a supplementary technique for pulpal anesthesia in cases of irreversible pulpitis. Aims and Objective: The current clinical trial was undertaken to assess and compare the effectiveness of the conventional inferior alveolar nerve block (IANB) and the ILA technique utilizing the STA system for endodontic management of mandibular molars presenting symptomatic irreversible pulpitis. Materials and Methods: Patients diagnosed with symptomatic irreversible pulpitis inmandibular molar were allocated into two groups: Group I IANB (n=30) and Group II- STA system (n=30). The onset of anesthesia was evaluated using the electric pulp test, whereas for pain perception the Heft-Parker Visual Analog Scale score was recorded before, during, and after anesthesia. Post-anesthetic pain was recorded at 3 h, 24 h, and 1 week. The collected data was evaluated for effectiveness pain perception, and acceptability of the anesthetic technique, using appropriate statistical tests. Results: The mean time of onset for the Group II STA system (2.93±1.80) was significantly higher (P=0.0001) than Group I IANB (1.40±0.86). Pain at the site of injection was insignificant (P>0.05) between both groups. The severity of pain during the root canal procedure was significantly different (P<0.0001) in both cohorts. For both groups, the patient’s acceptance of the anesthetic procedure was statistically insignificant (P=0.21). Conclusions: The STA system reported similar effectiveness in terms of effectiveness, pain perception, and acceptability of anesthetic technique when compared to IANB. Hence, the primary anesthetic treatment for conducting endodontic procedures on molars with symptomatic irreversible pulpitis appears to be the utilization of the ILA-employing STA system.